FACTORS INFLUENCING WILD TURKEY POULT SURVIVAL IN SOUTHCENTRAL IOWA - Michael W. Hubbard; Dale L. Garner; Erwin E. Klaas (Wildlife Society Bulletin)
Abstract: Population models indicate that small changes in poult survival can contribute to large changes in population predictions. We used a proportional‐hazards model to evaluate the influence of habitat variables and individual characteristics on eastern wild turkey (Meleagris gallopavo silvestris) poult survival. A proportional‐hazards model with percent of area in woody cover and brood size was significant (χ2 = 6.10, df = 2, P = 0.047, n = 39). The risk of mortality to poults decreased by 2.5% for each 1.0% increase in the proportion of the area occupied in woody cover and increased by 17.9% for each additional poult above 8 in the initial brood. A decreasing risk of mortality associated with an increasing amount of woody cover was also observed for adult females on the same, highly‐interspersed, study area.